A Comparative Study of Disaster Literacy Between Santri and Ustadz/Ah in Islamic Boarding Schools - Yulianingsih, Elsa (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2025)
This study aims to: 1) determine the level of disaster literacy among santri (Islamic boarding school students) and ustadz/ah (teachers) in pesantren; 2) analyze the difference in disaster literacy levels between santri and public school students. This research uses a descriptive quantitative approach with a cross-sectional survey method. The research sample consisted of 306 respondents, comprising 300 students (santri and junior high school students) selected by convenience sampling from 3 pesantren and 3 public schools in East Kalimantan, and 6 science teachers. The research instrument was a closed-ended questionnaire with a 5-point Likert scale based on Brown et al.'s (2014) literacy model, which had been tested for validity (product moment > 0.5) and reliability (Cronbach's Alpha > 0.6). Data analysis techniques used descriptive statistics to categorize literacy levels (low, medium, high) and the Mann-Whitney U test to examine differences between groups due to non-normally distributed data. The results show that: 1) the disaster literacy level of ustadz/ah is higher than that of santri, with santri's literacy still dominated by the medium category and characterized by uncertain responses across various indicators; 2) although the Mann-Whitney test indicated a statistically significant difference (p<0.05) between santri and public school students, both groups face similar practical challenges, namely the dominance of medium-level literacy and comparable patterns of uncertainty.